Exploring the Role of Artificial Intelligence in Enhancing English Teachers' Pedagogical Competence: a Case Study in an Indonesian Islamic School - Besse Sri Widistari; Mujahidah; Arqam (Universitas Islam Negeri Palopo, 2026)
This study investigates the role of Artificial Intelligence (AI) in enhancing the pedagogical competence of English teachers in a madrasah context. As AI technologies become increasingly integrated into educational practices, understanding their impact on teachers’ instructional capabilities is essential, particularly in underexplored settings such as Islamic secondary education. This study employed a qualitative case study design involving five English teachers at MTs As’adiyah Puteri Pusat Sengkang, Indonesia. Data were collected through semi-structured interviews, classroom observations, and document analysis, and analyzed using thematic analysis supported by NVivo. The findings reveal that AI plays a multifaceted role in teaching practices. First, it enhances efficiency by supporting lesson planning and material development. Second, it functions as an instructional assistant by facilitating content delivery and providing immediate feedback. Third, it contributes to learning enhancement by increasing student engagement and promoting learner autonomy. However, several challenges were identified, including students’ overreliance on AI, ethical concerns, and limited teacher control over its use. This study concludes that AI serves as a pedagogical partner rather than a replacement for teachers. It highlights the need for professional development and ethical guidelines to support effective AI integration. The findings contribute to the growing discourse on AI in education by providing context-specific insights from madrasah settings. Keywords: Artificial Intelligence; English Language Teaching; Islamic Education; Pedagogical Competence; Teacher Professional Development